2020
DOI: 10.3390/foods9010094
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Screen of the Color and Water Content of Fresh-Cut Potato Tuber Slices Using Hyperspectral Imaging Coupled with Multivariate Analysis

Abstract: Color index and water content are important indicators for evaluating the quality of fresh-cut potato tuber slices. In this study, hyperspectral imaging combined with multivariate analysis was used to detect the color parameters (L*, a*, b*, Browning index (BI), L*/b*) and water content of fresh-cut potato tuber slices. The successive projections algorithm (SPA) and competitive adaptive reweighted sampling (CARS) were used to extract characteristic wavelengths, partial least squares (PLS) and least squares sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…PLSR combined with feature wavelength selection methods such as selected interval partial least squares regression (iPLSR) yielded the R 2 P as high as 0.91 [ 85 , 91 ]. Then, the hyperspectral imaging was employed to measure the color index (L*, a*, b*, browning index (BI), L*/b*) of fresh-cut potato tuber slices [ 77 ]. Compared to PLSR, higher accuracies were obtained by using least squares support vector machine (LSSVM) and feature wavelength selection methods including SPA and CARS.…”
Section: Applications For Tuber Quality Assessmentmentioning
confidence: 99%
“…PLSR combined with feature wavelength selection methods such as selected interval partial least squares regression (iPLSR) yielded the R 2 P as high as 0.91 [ 85 , 91 ]. Then, the hyperspectral imaging was employed to measure the color index (L*, a*, b*, browning index (BI), L*/b*) of fresh-cut potato tuber slices [ 77 ]. Compared to PLSR, higher accuracies were obtained by using least squares support vector machine (LSSVM) and feature wavelength selection methods including SPA and CARS.…”
Section: Applications For Tuber Quality Assessmentmentioning
confidence: 99%
“…Therefore, HSI can get both external characteristic information and internal molecular information of samples, providing the possibility for the comprehensive analysis of samples. In recent years, the quality assessment and variety classication of HSI in the elds of agriculture [14][15][16] and food [17][18][19][20][21][22] have attracted increasing attention. It is possible to rapidly and accurately identify the geographical origins of Radix Glycyrrhizae through HSI.…”
Section: Introductionmentioning
confidence: 99%
“…This model had an R c 2 value of 0.8514, RMSEC of 0.3259, R p 2 value of However, the research of the above scholars is aimed at the whole potato, not fresh-cut potato slices. One study by Xiao et al 29 reported the use of HSI for the prediction of water content in fresh-cut potatoes, and the optimal model was established on the full wavelengths, instead of characteristic wavelengths. At present, there is no report on starch content detection in fresh-cut potatoes.…”
Section: Model Comparison and Discussionmentioning
confidence: 99%